2021
DOI: 10.1155/2021/1376859
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transverse Aortic Constriction in Mice Based on the Specific Recruitment of Leukocytes to the Hypertrophic Myocardium and the Aorta Ascendens

Abstract: Transverse aortic constriction (TAC) is a model that mimics pressure overload-induced left ventricular (LV) hypertrophy in mice. Alterations in immune cell functionality can promote cardiac and vascular remodeling. In the present study, we characterized the time course in innate immune cell dynamics in response to TAC in the different tissues of mice. It was determined whether TAC induces a characteristic leukocyte-driven immune response in the myocardium, aorta ascendens and descendens, spleen, blood, and dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We and others have previously shown biphasic upregulation of cardiac IL-1β during experimental pressure-overload, with a rapid increase (from 3 days post-TAC 21 ), followed by a second progressive increase (from 3-8 weeks post-TAC). 11,24 Our cardiac immunohistochemical analyses revealed increased cardiac IL-1β levels, notably in areas of macrophage accumulation and interstitial fibrosis (Suppl. Fig.…”
Section: Only Early Anti-il-1β Treatment Moderately Affects Cardiac I...mentioning
confidence: 92%
See 2 more Smart Citations
“…We and others have previously shown biphasic upregulation of cardiac IL-1β during experimental pressure-overload, with a rapid increase (from 3 days post-TAC 21 ), followed by a second progressive increase (from 3-8 weeks post-TAC). 11,24 Our cardiac immunohistochemical analyses revealed increased cardiac IL-1β levels, notably in areas of macrophage accumulation and interstitial fibrosis (Suppl. Fig.…”
Section: Only Early Anti-il-1β Treatment Moderately Affects Cardiac I...mentioning
confidence: 92%
“…We and others have previously shown biphasic upregulation of cardiac IL-1β during experimental pressure-overload, with a rapid increase (from 3 days post-TAC 21 ), followed by a second progressive increase (from 3 to 8 weeks post-TAC). 9,22 Pressureoverload not only activates inflammatory pathways in the heart, but also systemic innate immune cell activation, which in the chronic setting leads to splenomegaly. 22,23 We found that both early and late anti-IL-1β treatment significantly reduced spleen weight at 8 weeks post-TAC (Fig.…”
Section: Only Early Anti -Il-1 Treatment Moderately Affects Cardiac ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, flow cytometry is a versatile and powerful tool utilized in wide variety of fields, including immunology, haematology, oncology, virology, and microbiology. In immunology, flow cytometry is used to identify and characterize different types of immune cells, to study the immune response to infection or disease, and to develop new immunotherapies [6,7]. In haematology, flow cytometry is helpful in diagnosing and monitor blood diseases, such as leukaemia, lymphoma, and anaemia.…”
Section: Introductionmentioning
confidence: 99%